I am trying to prove that $\sin(x)-\cos(x)\ge 1$ for every $x$ in the interval $[\frac{\pi}2,\pi]$.

I started by assuming that it is false, i.e. there exists an $x$ for which $\sin(x)-\cos(x)<1$. In the next step I got stuck, since I wanted to take the square of each side of the inequality, so I can get $[\sin(x)-\cos(x)]^2<1$, but this is not true, since $a<b$ doesn't imply $a^2<b^2$. Can you assist me to prove this statement by contradiction? Is there also a way to prove it without contradiction? Thank you.

  • $\begingroup$ Perhaps simpler is to consider that $\cos\left(x+\frac{\pi}{4}\right)=\frac{1}{\sqrt2}(\cos x - \sin x)$ and manipulate this expression a bit. $\endgroup$ – πr8 Jan 14 '17 at 12:59
  • $\begingroup$ Just as a warning, squaring doesn't preserve inequality. $-2 < 1$ but $(-2)^2 > 1^2.$ $\endgroup$ – B. Goddard Jan 14 '17 at 13:06
  • $\begingroup$ Exactly ! It doesn't preserve the inequality, and in order to preserve it, I assume the thing I am trying to prove ! $\endgroup$ – user2899944 Jan 14 '17 at 13:08

Just for a different tack: $x$ is a 2nd-quadrant angle, so $\sin x$ and $-\cos x$ are the (positive) lengths of the legs of the corresponding triangle of hypotenuse $1$. So by triangle inequality, $\sin x + (-\cos x) \geq 1.$


I think squaring was a good idea. Note that $$ \sin x - \cos x \geq 1\\ (\sin x - \cos x)^2 \geq 1\\ \sin^2 x -2\sin x \cos x + \cos^2x \geq 1\\ (\sin^2 x + \cos^2 x) - 2\sin x \cos x \geq 1\\ 1 - 2\sin x\cos x \geq 1\\ -2\sin x \cos x \geq 0 $$ which is true as long as $\sin x$ and $\cos x$ have opposite signs (or one of them is zero), which is fulfilled on the interval $[\pi/2, \pi]$.

Now, we may have introduced additional solutions while squaring. However, since at the domain in question we clearly have $\sin(x) - \cos x \geq 0$, it is fine.

  • $\begingroup$ How can I square based on the assumption that sin(x)-cos(x)>=1 when this is what I am trying to prove in the first place? $\endgroup$ – user2899944 Jan 14 '17 at 13:04
  • $\begingroup$ @user2899944 When we square, we're assuming that $\sin x - \cos x \geq 0$. This is not what we want to prove, but significantly weaker, and a lot easier to show, for instance by pointing out that $\sin x \geq 0$ and $0 \geq \cos x$. $\endgroup$ – Arthur Jan 14 '17 at 13:10

$$\sin x - \cos x\ge1\text{ for }x\in[\pi/2,\pi]$$

$$ \iff \sin (x+\pi/2) - \cos (x+\pi/2)\ge 1\text{ for }(x+\pi/2)\in[\pi/2,\pi]$$

$$\iff \cos y + \sin y \ge 1 \text{ for }y\in[0,\pi/2]$$

Now, $\cos,\sin$ are both positive on this interval, so squaring doesn't lose any information:

$$\iff (\cos y + \sin y)^2=1+2\cos y\sin y \ge 1 \text{ for }y\in[0,\pi/2]$$

$$\iff \sin 2y\ge 0 \text{ for }y\in[0,\pi/2]$$

after noting that $\sin 2\theta = 2\sin\theta\cos\theta$


$$\iff \sin 2y\ge 0 \text{ for }2y\in[0,\pi]$$

$$\iff \sin z\ge 0 \text{ for }z\in[0,\pi]$$

and, $\sin$ is $\ge0$ on this interval, so all of the statements above are true, and we're done!


Avoid squaring as it immediately introduces extraneous solution(s) which deserves elimination.

Let $x=2y,\dfrac\pi2\le2y\le\pi\iff\dfrac\pi4\le y\le\dfrac\pi2$

$\sin2y=2\sin y\cos y$ will be $\ge\cos2y+1=2\cos^2y$

$\iff2\sin y(\cos y-\sin y)\ge0$

Now for $\dfrac\pi4\le y\le\dfrac\pi2,\sin y>0$

So, we need $\cos y-\sin y\ge0$

But $\cos y-\sin y=\sqrt2\sin\left(\dfrac\pi4-y\right)$ and $\dfrac\pi4\le y\le\dfrac\pi2$

Can you take it from here?


Since you're over $[\pi/2,\pi]$, you have that $\sin x\ge0$; moreover $1+\cos x\ge0$, so it's legal to square $\sin x<1+\cos x$, getting $$ \sin^2x<1+2\cos x+\cos^2x $$ In other words, recalling that $1-\sin^2x=\cos^2x$, $$ 2\cos^2x+2\cos x>0 $$ and so $$ \cos x(1+\cos x)>0 $$ which is false, because in the given interval, $\cos x\le0$ and $1+\cos x\ge0$.

For a direct proof, write $x=2y$, so you have $$ \sin x-\cos x=2\sin y\cos y-\cos^2y+\sin^2y $$ You have to prove $$ 2\sin y\cos y-\cos^2y+\sin^2y\ge 1=\sin^2y+\cos^2y $$ for $y\in[\pi/4,\pi/2]$, that becomes $$ \sin y\cos y-\cos^2y\ge0 $$ This is true for $y=\pi/2$, so we can look at $[\pi/4,\pi/2)$, where the inequality becomes $$ \cos y(\tan y-1)\ge0 $$ which is true.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.